Efeitos da injeção de lidocaína 1% sem conservantes, em olhos de coelhos da raça Nova Zelândia Branco com uveíte - Barros Sobrinho, Alexandre Augusto Franchi de [UNESP] (2014)
We studied the effects of preservative-free 1% lidocaine on parameters of uveitis. Thirty rabbits comprised the study, ten forming a control group (CG). The others, with experimental uveitis, were divided into uveitis treated group (UTG) and uveitis non-treated group (UNTG). CG group received 0.2 mL of preservative-free 1% lidocaine, via intracameral route. UTG and UNTG animals received 0.2 mL of preservative-free 1% lidocaine and 0.2 mL of saline (NaCl 0.9%), respectively, twelve hours after the induction of uveitis, via the same route and with the same criteria. The assessment of pupil diameter (PD) was made by pachymetry, at the following times: baseline (PD0') until the 10th minute; every minute, until the 30th minute; every 5 minutes, and up to 60 minutes, every 10 minutes. We conducted a clinical examination, which included the evaluation of the conjunctival hyperemia, chemosis and edema of the cornea. Intraocular pressure (IOP) was measured by applanation tonometry. We conducted quantitative analyses of the flare of the aqueous with a laser flarimetry. The hexagonality, cell density, cell area, coefficient of variation and corneal thickness were evaluated in a non-contact specular microscope. Assessments occurred at baseline (M0) in all groups, 12 hours after induction of uveitis in groups UTG and UNTG (M1), 1 hour (M2), 12 hours (M3) and 24 hours (M4) after intracameral injection in all groups. Aliquots of aqueous humor were evaluated for pH and for the quantification of proteins. Differences were considered significant when p ≤ 0.05. As for the pupillary diameter, there was a significant difference (p <0.05) at all times between the CG and the other groups (UTG and UNTG), being higher in CG, followed by UTG and the UNTG. As for the PIO, all groups showed differences between M0 and the other times (p <0.05), being higher in M0. Regarding corneal thickness there was a significant difference between M3 and the other times ...